Mitochondrial DNA in extracellular vesicles declines with age - Lazo, Stephanie; Noren Hooten, Nicole; Green, Jamal; Eitan, Erez; Mode, Nicolle A.; Liu, Qing‐Rong; Zonderman, Alan B.; Ezike, Ngozi; Mattson, Mark P.; Ghosh, Paritosh; Evans, Michele K. (Aging cell, 2021)
The mitochondrial free radical theory of aging suggests that accumulating oxidative damage to mitochondria and mitochondrial DNA (mtDNA) plays a central role in aging. Circulating cell‐free mtDNA (ccf‐mtDNA) isolated from blood may be a biomarker of disease. Extracellular vesicles (EVs) are small (30–400 nm), lipid‐bound vesicles capable of shuttling proteins, nucleic acids, and lipids as part of intercellular communication systems. Here, we report that a portion of ccf‐mtDNA in plasma is encapsulated in EVs. To address whether EV mtDNA levels change with human age, we analyzed mtDNA in EVs from individuals aged 30–64 years cross‐sectionally and longitudinally. EV mtDNA levels decreased with age. Furthermore, the maximal mitochondrial respiration of cultured cells was differentially affected by EVs from old and young donors. Our results suggest that plasma mtDNA is present in EVs, that the level of EV‐derived mtDNA is associated with age, and that EVs affect mitochondrial energetics in an EV age‐dependent manner. Mitochondrial dysfunction plays a central role in aging. A portion of circulating cell‐free mitochondrial DNA (mtDNA) isolated from blood is present in extracellular vesicles (EVs), which are small, lipid‐bound vesicles that shuttle macromolecules as part of intercellular communication systems. The level of EV‐derived mtDNA declines with age, and these EVs affect mitochondrial energetics in an EV age‐dependent manner.